A Novel Mechanical Component Retrieval Approach Based on Differential Moment. (9th July 2013) - Guo, Kehua; Liu, Wu; Song, Hong
Abstract : The differential geometry and moment invariants are important approaches in pattern recognition and artificial intelligence. In this paper, a novel approach for mechanical component retrieval is reported. This approach combines local (spatial curvature) signatures and global (moment) features of 3D mechanical component. Mean curvatures are integrated into the computation of 3D moment invariants, and differential moment invariants are constructed. Experiments indicate that differential moment invariants have a lower computation complexity than traditional 3D image retrieval approaches without reducing the retrieval rate.